1994
DOI: 10.1002/ana.410360309
|View full text |Cite
|
Sign up to set email alerts
|

Increased transforming growth factor‐β, interleukin‐4, and interferon‐γ in multiple sclerosis

Abstract: The inflammatory nature of multiple sclerosis (MS) implicates the participation of immunoregulatory cytokines, including the T-helper type 1 (Th1) cell-associated interferon-gamma (IFN-gamma), the Th2 cell-related interleukin-4 (IL-4), and the immune response-downregulating cytokine transforming growth factor-beta (TGF-beta), but proof for their involvement in MS has been lacking. By adopting in situ hybridization with complementary DNA oligonucleotide probes for human IFN-gamma IL-4, and TGF-beta, the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
1
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(74 citation statements)
references
References 36 publications
4
68
1
1
Order By: Relevance
“…The IL-4 production by T cells from the HRs accords with the finding of high numbers of IL-4-producing cells in blood and cerebrospinal fluid of patients with MS, 42 and with the increases in the levels of messenger RNA for IL-4 (along with IL-2, IL-4, IL-6, IFN-c and IL-1a) in spinal cord samples from mice during the acute phase of EAE. 43 By contrast, a decrease in the IL-4 production by proteolipid protein-stimulated T-cell clones from patients with MS during acute attacks has also been reported.…”
Section: Cd4supporting
confidence: 80%
“…The IL-4 production by T cells from the HRs accords with the finding of high numbers of IL-4-producing cells in blood and cerebrospinal fluid of patients with MS, 42 and with the increases in the levels of messenger RNA for IL-4 (along with IL-2, IL-4, IL-6, IFN-c and IL-1a) in spinal cord samples from mice during the acute phase of EAE. 43 By contrast, a decrease in the IL-4 production by proteolipid protein-stimulated T-cell clones from patients with MS during acute attacks has also been reported.…”
Section: Cd4supporting
confidence: 80%
“…However, in a neurodegenerative disease model, transgenic overexpression of TGF-b1 in astrocytes exacerbates the disease pathology (WyssCoray et al 1997). In patients with multiple sclerosis, high levels of TGF-b1 mRNA expression in mononuclear peripheral cells have been associated with reduced disability, disease duration, and disease brain activity (Link et al 1994;Söderström et al 1995;Bertolotto et al 1999), although clinical trials of TGF-b treatment of patients with multiple sclerosis were terminated because of non-neurological toxicity (Wiendl et al 2000).…”
Section: Injury and Repairmentioning
confidence: 99%
“…Regarding MS, it has been shown that IL-17 is elevated in immune cells within the CNS and at the periphery and that it contributes to the pathogenesis of the disease, eg through distortion of the blood-brain-barrier [19][20][21] . It has also been shown that IFN-γ-producing cells are present within the CNS and at the periphery of MS patients [22] , and that treatment of MS patients with IFN-γ exacerbates the disease [23] . Therefore, inhibiting IL-17 and IFN-γ generation is relevant when modulating the EAE course and also has relevance when evaluating therapeutic efficiency in MS.…”
Section: Wwwchinapharcom Blaževski J Et Almentioning
confidence: 99%